Valproic acid induced selective apoptosis of ocular fibrous tunic in mice fetuses. Issue 19 (16th August 2022) - Manthos, Kyriakos; Theotokis, Paschalis; Dermitzakis, Iasonas; Avramidou, Eleni; Meditskou, Soultana; Manthou, Maria Eleni; Emmanouil‐Nikoloussi, Elpida‐Niki
Abstract: Background: Valproic acid (VPA), a prescribed drug commonly used for various neurological perturbations, has been implicated in teratogenic inflictions on developing fetuses during pregnancy. The purpose of this research was to delineate the gross morphological and histological effects of VPA in the developing eye tunics and lens. Methods: A time‐dependent administration of 500 mg/kg VPA to BALB/c groups of female mice was coordinated during organogenesis (gestational days 7, 8, and 9) and compared to controls that received normal saline. Seized fetuses were checked for macroscopic eye anomalies, histological malformations with Azan trichrome staining, and levels of apoptotic activity with the terminal deoxynucleotidyl transferase‐mediated nick end labeling (TUNEL) assay. Results: Histochemical analysis showed that VPA‐treated groups exhibited collagen deficiency (2.5–50% decrease in aniline blue intensity) and a marked increase in TUNEL‐positive cells ( p  < .05) in corneal stroma and sclera/choroid layers while less was detected in retina and lens, when compared to controls. Conclusions: Since the evaluation of the inner structures did not manifest major differences, we conclude that VPA teratogenic influence display eclectic toxicity, as seen by increased apoptosis to eye layers with high degree fibrous context, particularly the outer tunics.